Different outcomes of phonemic verbal fluency in Parkinson’s disease patients with subthalamic nucleus deep brain stimulation - Aline Juliane Romann; Bárbara Costa Beber; Maira Rozenfeld Olchik; Carlos R M. Rieder (Arquivos de Neuro-Psiquiatria)
ABSTRACT Subthalamic nucleus deep brain stimulation (STN-DBS) is a surgical technique to treat motor symptoms in patients with Parkinson’s disease (PD). Studies have shown that STN-DBS may cause a decline in verbal fluency performance. We aimed to verify the effects of STN-DBS on the performance of phonemic verbal fluency in Brazilian PD patients. Sixteen participants were evaluated on the Unified Parkinson’s Disease Rating Scale - Part III and for phonemic fluency (“FAS” version) in the conditions of on- and off-stimulation. We identified two different patterns of phonemic verbal fluency outcomes. The results indicate that there may be no expected pattern of effect of bilateral STN-DBS in the phonemic fluency, and patients may present with different outcomes for some reason not well understood.